Racismo antinegro y derecho en el Perú: análisis del caso Algendones - Xavier Pinto Coelho, Luana (2023)
Drawing on the critical race theory, this text proposes to investigate how the mechanisms of institutional racism act in the different spheres of the State through an in-depth study of the case of Algendones. Using documentary sources, but also interviews, the work develops a socio-legal analysis of the case of denunciation of racial discrimination in Peru. The methodology is based on storytelling or the experience of the victim in different parts of the process. It starts from the premise that anti-black racism is a system of oppression historically built from the colonial past as a legacy of racial enslavement. This legacy has an impact on legal practice and theory by limiting the scope of the category of the human and, therefore, of the subject of law. Specifically, the category of fungibility is used as an element of survival of racial slavery that acts as an impediment to prosecute a demand for the dignity of a black woman. The study reaches the conclusion that legal recognition of racism as a limited phenomenon restricted to racial discrimination limits the fight to its long-lasting effects. In the same way, the legislative and institutional options to combat discrimination are insufficient to challenge existing institutional/ structural racism and, thus, do not promote changes or ruptures in (racial) power relations.